Professori Ljubinkae Basotovae IN MEMORIAM (Annual of the Faculty of Philosophy in Skopje, 2020)
Ljubinka Basotova, PhD, professor at the Faculty of Philosophy in Skopje,a renowned classical philologist, pedagogue, scholar, an eminent translatorof classical languages, passed away this year, on 18 June 2020. In memory ofher fulfilled life and versatile professional career, let us briefly reflect on thecontribution and efforts that professor Ljubinka Basotova made for the Macedonianscientific, cultural and education community with her numerousworks, research papers, translations, verse translations and textbooks, as wellas her scholarly and pedagogical engagement. Even though the focal points inwhich her exquisite intellectual capacity manifested were mainly in science,translation and teaching, which by their nature, and in case her particularly,are inextricably interlaced in the best way possible, professor Basotova alsohad erudition and enthusiasm to be committed and successful in other socialactivities. This sad occasion and tradition call for focusing first on the usualfacts of the professor’s professional biography.